Inherent safety for sustainable process design of process piping at the preliminary design stage - Athar, M. (2019)
Risk assessment is an accepted approach used worldwide to improve the sustainability of either the existing process plant or the design of a new installation. In the current practices, risk assessment is normally performed once the design has been completed. A better approach is to perform risk assessment at the initial design stages with the application of inherent safety concept to achieve the sustainable cleaner chemical process. This paper consolidates a new technique to improve the safety level of process piping from potential fire risk using the inherent safety concept. Inherently safer process piping (ISPP) technique utilizes fundamental of fluid flow to predict the potential damage from a major fire accident. A relative ranking of process streams is used to identify the critical process streams that have higher chances of damage. Risk assessment is performed to check if the potential fire exceeds the acceptance criteria or not. If the risk is not in the acceptable range, inherent safety principle is used to reduce the risk to the acceptable limit. The ISPP technique is validated using a case study of methanol process plant. This technique could be used to facilitate design practitioners to incorporate inherent safety at the early design stage. Â© 2018 Elsevier Ltd